Optimizing Protein Extraction from Cowpea (Vigna unguiculata) and Pigeon Pea (Cajanus cajan) via Central Composite Design (CCD) - Flores Annabelle C; Aidasani Norli L; Jocson Stanly Adam C (Research Synergy Foundation, 2025)
Plant-based proteins have gained popularity over the last decade due to their sustainability and favorable environmental impact. Proteins from underused legumes can be converted into value-added compounds, helping to sustain protein demand. This study sought to develop a standardized and improved procedure for producing plant protein concentrate from cowpea and pigeon pea. Protein extraction parameters were improved using the Response Surface Methodology with a Central Composite Design (RSM-CCD). The factors optimized were solid-liquid ratio, pH basic, and pH acidic, each varied within ranges defined by the CCD model to evaluate their effect on protein yield and content. The protein extraction processing parameters derived from the optimization trials were used to scale up protein powder production. The upgraded production yield and protein content for cowpea protein powder are 6.77% and 72.6%, respectively, while pigeon pea protein powder yields 6.01% and 63.8%. Statistical analysis confirmed the model adequacy (cowpea: R2=0.9399 for % protein, R2=0.9250 for % yield; pigeon pea: R² = 0.7836 for % protein, R² = 0.7704 for % yield; p < 0.05). Improved yield and protein content can enhance the development of low-cost, sustainable, and culturally inclusive (Halal/vegetarian) protein ingredients, supporting both the food industry and nutrition science by providing alternative protein sources that reduce reliance on imported soy and animal proteins. This study demonstrates that RSM-CCD is a robust and efficient approach for optimizing plant protein extraction parameters, offering valuable insights for functional food formulation and industrial-scale protein production.